KONTRIBUSI KEMANDIRIAN SISWA DAN SARANA PRAKTIKUM TERHADAP HASIL BELAJAR MATA DIKLAT MELAKUKAN PERBAIKANPHERIPERALKELAS X TEKNIK KOMPUTER JARINGAN (TKJ)SMK NEGERI 1 SINTUAK TOBOH GADANG - Anisa Novia Sari; Kasman Rukun; Thamrin Thamrin (Universitas Negeri Padang, 2018)
The purpose of this study is to reveal the contribution of independence students and lab work are jointly or singly against the results of the study. This research population amounted to 58 people and sample totaling 37 students of class X TKJ in SMK Negeri 1 Sintuak Toboh Gadang. The technique of sampling was done randomly (Simple Random Sampling). Data about student learning result obtained from subjects teachers repair pheriperal grade X TKJ in SMK Negeri 1 Sintuak Toboh Gadang. While data on independence students and lab work are collected through the now presented to student by using Likert scale which have tested the validity and realibility. The results of the analysis of the data shows that (1) independence students and lab work are jointly contribute significantly to student learning outcomes in SMK Negeri 1 Sintuak Toboh Gadang of 43,42%, (2) independence students contributed significantly to the results of the study amounted to 23,61%, (3) lab work contributed significantly to the results of the study at SMK Negeri 1 Sintuak Toboh Gadang of 37,21%. Keywords: Independence students, Lab Work, The Results Of The Study